Bombs bursting in air : American, Russian and European Ballistic Missile Defense Perception - Ziegler, Jonathan G. (2008)
The issue of ballistic missile defense (BMD) is not a new one, but historical factors are very important in understanding BMD policies. This work is an attempt to understand the policies and perceptions towards BMD and their reasons. To that end, it seeks to answer the question: What have been the policies and perceptions of BMD in the past 25 years in the US, Russia and Europe and how do they reflect the strategic culture of each? The work begins with an explanation of BMD, its applications, the technical questions surrounding it, deterrence, strategic culture and the issue of space-deployed weapons. It then describes US strategic culture, US BMD policy from the early 1980s up to and beyond the current administration and its plans to deploy a European based BMD. Next, the work does essentially the same for Russia, describing Russia strategic culture and tracing BMD policy from Gorbachev through Putin and speculating on Dmitry Medvedev’s possible role and policies. European strategi.